Uno's garden - Base, Graeme (New York : Abrams Books for Young Readers, 2006)
Uno builds a home and garden in the magnificent forest among the playful puddlebuts and feathered frinklepods, but as the place becomes more and more popular, it is overtaken by tourists and buildings until the forest and animals seem to disappear altogether.
Keywords: Nature; Cities and towns; Pollution; Imaginary creatures; Change; Counting